THE STUDY OF PREVALENCE, MANAGEMENT AND OUTCOME OF MUSCULOSKELETAL INJURIES IN RUNNERS: A COMPREHENSIVE SYSTEMATIC REVIEW - Yuli Firlando, Afdhal; Assyifa, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Running's popularity has surged globally, doubling in the last decade, due to its accessibility and health benefits. However, it carries a high injury risk, especially in lower extremities, with rates varying by distance. Understanding injury prevalence and risk factors is essential. This study aims to serve a comprehensive systematic review to analyze the prevalence, management and outcome of musculoskeletal injuries in runners based on literatures of the last 10 years. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 655 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, ten articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Musculoskeletal injuries in runners are common. Tailored interventions like gait retraining and targeted exercises can reduce their incidence and severity. Further research is needed to assess long-term effects and develop standardized prevention and management protocols for diverse running populations.